New work by a new generation. (Regina, Sask. : Norman Mackenzie Art Gallery, University of Regina, 1982)
Houle, Robert ; Longfish, George C. ; Paul, Leonard ; Poitras, Edward ; White, R. Lee ; Williams, Dana A. ; Fonseca, Harry ; Fife, Phyllis ; Emerson, Larry ; Coffin, Douglas ; Cisneros, Domingo ; etc.
New work by a new generation, Norman Mackenzie Art Gallery, University of Regina, Regina, July 9 to August 29, 1982
boek